Single cell analysis of iNKT cell heterogeneity, phenotype, and function - Kane, Harry (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2022)
Innate T cells, including CD1d-restricted invariant natural killer T (iNKT) cells, are characterized by their rapid activation in response to non-peptide antigens, such as lipids. While the transcriptional profiles of naive, effector and memory adaptive T cells have been well studied, less is known about transcriptional regulation of different iNKT cell activation states. In this study, using single cell RNA-sequencing, we performed longitudinal analysis of activated iNKT cells and explored iNKT cell heterogeneity, generating a transcriptomic atlas of iNKT cell activation states. We found that transcriptional signatures of activation are highly conserved among heterogeneous iNKT cell populations, including NKT1, NKT2, and NKT17 subsets, and human iNKT cells. Strikingly, we found that regulatory iNKT cells, such as adipose iNKT cells, undergo blunted activation, are heterogeneous, and display enrichment of memory-like cMAF+ and KLRG1+ iNKT cell populations. Moreover, we identify a conserved cMAF-associated transcriptional network among NKT10 cells, providing novel insights into the biology of regulatory and antigen experienced iNKT cells.
APPROVED
Keywords: Immunology; scRNA-Seq; Adipose tissue; iNKT cell